Construction of basketball shoe sole design by using bezier curves / Noorehan Awang ... [et al.] - Awang, Noorehan; Zaidi, Dalila Aqilah; Md Fuad, Nur Farehah; Azlan, Fatin Athira (UiTM Cawangan Negeri Sembilan, 2021)
Computer-aided geometric design (CAGD) plays an important role in the design world. In designing curves and surtaces, CAGD deals with mathematical expressions to regulate shapes by Bizzarri & Lavicka (2011). CAGD has several types of polynomial curves such as Bezier, Said-Ball, Wang-Ball, and DP curves. There are some common and specific properties in these curves. All of them are defined in terms of the total sum of their mixing and control points functions. Each of the polynomials has its own speciality as stated by Bizzarri & Lavicka (2011). This study chooses to use the Bezier curve to construct the shape of a basketball shoe sole. Bezier curve is an important tool used in vector graphics to model smooth curves that can be scaled indefinitely. The principle of continuity is then extended to an aim of smoothness or visually nice curves and surfaces as claimed by (Yahaya, 2015). Shoe is footwear that every human uses since it gives protection to their feet. There are a variety of types of shoes to be used by humans. The design of the shoe sole is very important and people need to consider it so they can use it for a long time. The focus of this study is on sport shoes which are basketball shoes that are usually used by the basketball players. This study wants to differentiate the degree evaluation from lower degree to higher degree for Bezier curve of basketball shoe pattern and to determine the computation times of the outsole of the shoe. Figure 1(a) shows the original figure of the basketball shoe sole while the second figure shows the drawing of the basketball shoe sole on the graph paper (Figure 1(b)).